The Crucial Role of Teacher Support in Enhancing Willingness to Communicate, Professional, Communicative and Lexical Competences - Borasheva, Aybolgan (Indonesian Journal Publisher, 2024)
Effective communication skills are essential in education as they significantly enhance student learning experiences and outcomes. This article explores the role of Willingness to Communicate (WTC) and communicative competence in language learning, emphasizing the importance of teacher support in fostering these competencies. Key factors influencing WTC, such as self-communicative competence, communication apprehension, and individual psychological traits, are discussed. The article highlights the pivotal role of teacher involvement, immediacy, and autonomy support in promoting student engagement, self-efficacy, and language proficiency. Furthermore, the development of lexical competence and the use of innovative teaching approaches, such as flipped classrooms and collaborative learning activities, are examined as effective strategies for improving communication skills. The article underscores the importance of creating supportive classroom environments that reduce communication anxiety and promote active participation. Ultimately, the integration of robust teacher support practices and ongoing professional development is critical for enhancing communicative competence and ensuring long-term academic and professional success for students.